2002
DOI: 10.1580/1080-6032(2002)013[0094:osihti]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Humans Training in a Cold, Moderate Altitude Environment and Their Response to a Phytochemical Antioxidant Supplement

Abstract: An increased level of oxidative stress was associated with high levels of physical exertion of training in a cold environment at moderate altitude. The antioxidant mixture tested did not attenuate the mean oxidative stress levels in the entire group of test subjects, but it may have reduced the oxidative stress of some individuals with low initial antioxidant status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 57 publications
(119 reference statements)
9
47
1
Order By: Relevance
“…Earlier studies have shown increased levels of oxidative stress associated with physical work at moderate altitude over a shorter period of time than our study, 11 -24 days (Araneda et al 2005;Chao et al 1999;Pfeiffer et al 1999;Schmidt et al 2002;Vasankari et al 1997), and 12 hypoxic training sessions during 6 weeks (Pialoux et al 2006). However, in those studies no sedentary control groups were investigated at altitude and the objective was mainly to investigate the influence of antioxidant supplementation.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Earlier studies have shown increased levels of oxidative stress associated with physical work at moderate altitude over a shorter period of time than our study, 11 -24 days (Araneda et al 2005;Chao et al 1999;Pfeiffer et al 1999;Schmidt et al 2002;Vasankari et al 1997), and 12 hypoxic training sessions during 6 weeks (Pialoux et al 2006). However, in those studies no sedentary control groups were investigated at altitude and the objective was mainly to investigate the influence of antioxidant supplementation.…”
Section: Discussionmentioning
confidence: 43%
“…In particular, it is known that exposure to altitude combined with exercise (Araneda et al 2005;Bailey et al 2001;Chao et al 1999;Pfeiffer et al 1999;Schmidt et al 2002), and even exposure to altitude in resting conditions (Bailey et al 2001), increases reactive oxygen species (ROS) levels/formation, especially in lung and blood. On the other hand, acute physical work per se is a contributor to oxidative stress where mitochondria represent the major source of free radicals (Bailey et al 2001;Bailey et al 2004;Sen 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, the lower the sum total of carotenoid plasma concentration is, the higher the plasma lipoperoxidation marker (6) is. Among the antioxidant complex supplements given to athletes highly exposed to oxidative stress -especially in extreme conditions such as cold or high altitude -those containing b-carotene or multiple carotenoids at nutritional doses fight lipoperoxidation with more efficiency in individuals with low initial antioxidant status (5,10,45) . The origin of free radical production influences the effect of ingested antioxidant vitamins and carotenoids.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Taken together, this evidence strongly suggests that combining ALA and VE is better than monotherapy. In parallel, the ALA-VE mixture has been combined with other dietary antioxidants, such as vitamin C, beta-carotene, and selenium, and evaluated under several conditions of exercise, experimental diabetes, cold, age and cancer, and promising results have also been obtained [46][47][48][49][50][51].…”
Section: Synergism Between Lipoate and Tocopherolmentioning
confidence: 99%